Design and Construction of a Whole Cell Bacterial 4-Hydroxyphenylacetic Acid and 2-Phenylacetic Acid Bioassay - Dierckx, Seppe; Van Puyvelde, Sandra; Venken, Lyn; Eberle, Wolfgang; Vanderleyden, Jos (Frontiers in Bioengineering and Biotechnology, 2015)
Introduction Auxins are hormones that regulate plant growth and development. To accurately quantify the low levels of auxins present in plant and soil samples, sensitive detection methods are needed. In this study, the design and construction of two different whole cell auxin biosensors is illustrated. Both use the auxin responsive element HpaA as an input module and differ in output module. The first biosensor is combined with the gfp gene to produce a fluorescent biosensor. Whereas the second one is combined with the genes textit and phzS to produce a pyocyanin producing biosensor whose product can be measured electrochemically. \section{Results} The fluorescent biosensor is able to detect 4-hydroxyphenylacetic acid (4-HPA) and 2-phenylacetic acid (PAA) concentrations from 15 µM to 3 mM in a dose-responsive manner. The pyocyanin producing biosensor is able to detect 4-HPA concentrations from 1.9 µM to 15.625 µM and PAA concentrations from 15.625 µM to 125 µM, both in a dose-responsive manner. Conclusions A fluorescent whole cell auxin biosensor and an electrochemical whole cell auxin biosensor have been constructed and tested. Both are able to detect 4-HPA and PAA concentrations that are environmentally relevant in respect to plant growth.